2016
DOI: 10.1200/jco.2015.65.9128
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of a Radiomics Nomogram for Preoperative Prediction of Lymph Node Metastasis in Colorectal Cancer

Abstract: This study presents a radiomics nomogram that incorporates the radiomics signature, CT-reported LN status, and clinical risk factors, which can be conveniently used to facilitate the preoperative individualized prediction of LN metastasis in patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
1,146
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,500 publications
(1,172 citation statements)
references
References 38 publications
22
1,146
2
2
Order By: Relevance
“…Variations in acquisition and image reconstruction parameters can introduce changes that are not due to underlying biologic effects (17). Recently, CT has been the most widely used imaging modality, in consideration of its standard-of-care images (41). However, CT is also limited by the evolution of hardware and progress in informatics.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in acquisition and image reconstruction parameters can introduce changes that are not due to underlying biologic effects (17). Recently, CT has been the most widely used imaging modality, in consideration of its standard-of-care images (41). However, CT is also limited by the evolution of hardware and progress in informatics.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that radiomics signatures could be used to determine the risk of lymph-node metastasis in patients with colorectal and bladder cancer (23,24). Radiomics signatures have been reported to be important pretreatment prognostic predictors for progression-free and overall survival in patients with cancer (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these studies reported high values of accuracy, considering the radiomic signature estimated in a selected population and applied on an independent one from another institute, or from another body region, reporting high values of accuracy. 4,41,107 If this kind of validation is not feasible, some other evaluations should be performed, for example, using test and training sets, which should be taken from a separated cohort or at least considering leave-one-out cross-validation. 9 Even if texture analysis was carried out in the most rigorous way and if significant models that could predict tissue response to radiation or provide a characterization of tumour heterogeneity were found, the biological interpretation of these parameters remains one of the major questions about texture analysis.…”
Section: Limitations Of Texture Analysismentioning
confidence: 99%